KESANTUNAN BERBAHASA DALAM TUTURAN CERAMAH GUS IQDAM DAN IMPLIKASINYA TERHADAP PEMBELAJARAN - Aizatur Rodiyah; Junal Junal (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the formal form and pragmatic form of imperative in Gus Iqdam's speech. The method used in this research is descriptive with qualitative approach. The data source used in this research is Gus Iqdam's speech on social media. The data analysis used in this research is content analysis. The data that has been obtained in this study found imperative formal form and imperative pragmatic form. The types are transitive active imperative formal form, nontransitive active imperative formal form, passive imperative formal form, invitation imperative pragmatic form and prohibition imperative pragmatic form. The results of this study can be used as a source of reference, namely how to determine the speech that contains the formal form and pragmatic form of imperative.